3D-bioprinted, phototunable hydrogel models for studying adventitial fibroblast activation in pulmonary arterial hypertension. (1st January 2023) - Davis-Hall, Duncan; Thomas, Emily; Peña, Brisa; Magin, Chelsea M
Abstract: Pulmonary arterial hypertension (PAH) is a progressive disease of the lung vasculature, characterized by elevated pulmonary blood pressure, remodeling of the pulmonary arteries, and ultimately right ventricular failure. Therapeutic interventions for PAH are limited in part by the lack of in vitro screening platforms that accurately reproduce dynamic arterial wall mechanical properties. Here we present a 3D-bioprinted model of the pulmonary arterial adventitia comprised of a phototunable poly(ethylene glycol) alpha methacrylate (PEG-αMA)-based hydrogel and primary human pulmonary artery adventitia fibroblasts (HPAAFs). This unique biomaterial emulates PAH pathogenesis in vitro through a two-step polymerization reaction. First, PEG-αMA macromer was crosslinked off-stoichiometry by 3D bioprinting an acidic bioink solution into a basic gelatin support bath initiating a base-catalyzed thiol-ene reaction with synthetic and biodegradable crosslinkers. Then, matrix stiffening was induced by photoinitiated homopolymerization of unreacted αMA end groups. A design of experiments approach produced a hydrogel platform that exhibited an initial elastic modulus ( E ) within the range of healthy pulmonary arterial tissue ( E = 4.7 ± 0.09 kPa) that was stiffened to the pathologic range of hypertensive tissue ( E = 12.8 ± 0.47 kPa) and supported cellular proliferation over time. A higher percentage of HPAAFs cultured in stiffened hydrogels expressed the fibrotic marker alpha-smooth muscle actin than cells in soft hydrogels (88 ± 2% versus 65 ± 4%). Likewise, a greater percentage of HPAAFs were positive for the proliferation marker 5-ethynyl-2ʹ-deoxyuridine (EdU) in stiffened models (66 ± 6%) compared to soft (39 ± 6%). These results demonstrate that 3D-bioprinted, phototunable models of pulmonary artery adventitia are a tool that enable investigation of fibrotic pathogenesis in vitro .